Inhibition of Angiogenesis and Nitric Oxide Synthase (NOS), by Embelin & Vilangin Using in vitro, in vivo & in Silico Studies - Radhakrishnan Narayanaswamy; Majumder Shymatak; Suvro Chatterjee; Lam Kok Wai; Gnanamani Arumugam (Tabriz University of Medical Sciences, 2014)
Purpose: In recent year's anti-angiogenesis agents have been recognized as effective drugs for the treatment of solid tumors, this prompted us to conduct the present study. Methods: The anti-angiogenic activity of dimeric form of embelin (vilangin) was evaluated using endothelial cell (in vitro) and chorioallantoic membrane (CAM) egg yolk angiogenesis model (in vivo) and in addition the docking behaviour of human nitric oxide synthases (NOS) with four different ligands was evaluated along with their putative binding sites using Discovery Studio Version 3.1 (in silico) compared with the parent compound (embelin). Results: Vilangin exhibits 50% cytotoxic at 92 ± 1 µg/ml concentration level with reference to ECV 304 endothelial cells. Both vilangin and embelin, showed inhibitory effects on wound healing, single cell migration, nitric oxide production, and endothelial ring formation at 0.1 and 1.0 μg/ml concentration level. Similarly, CAM assay also showed inhibitory effect of vilangin and embelin with respect their reduction in length, size and junctions of blood capillaries compared to untreated egg yolk. Docking studies and binding free energy calculations revealed that vilangin has maximum interaction energy (-74.6 kcal/mol) as compared to the other investigated ligands. Conclusion: The results suggest that both vilangin and embelin attenuates angiogenesis in similar manner.